Loyalty, secrecy and revolutionary work: female underground operatives and narratives about Chinese female spies before and after 1949 - Zhang, A (2021)
This thesis is a study of civilian women mobilised by the Chinese Communist Party (CCP) and their wartime activities prior to the 1949 Communist takeover of China. Specifically, it investigates the kind of clandestine activities civilian women were mobilised to do – such as the gathering of intelligence and enemy sabotage, how civilian women came to be involved in the first place, and the reasons behind their mobilisation, especially according to CCP Woman-Work officials. It also considers whether civilian women acted or were expected by officials to act in ways similar to the “seductress-spy” stereotype which pervaded popular culture in China at that time. To do so, this thesis first explores popular Chinese ideas of female spies in the first half of the 20th century. It then looks at how civilian women were actually mobilised to engage in clandestine activities during the civil wars between the Nationalists and the Communists and the Sino-Japanese War. Lastly, it explores what happened when the demand for civilian women to engage in these activities decreased in the latter half of the 1940s, and how such women remembered their activities in the 1980s. It uses Republican Chinese periodicals, newspapers, rare published sources in both Chinese and Japanese, compiled volumes of CCP documents and declassified Nationalist and Communist archival materials from Chinese archives. It finds that civilian women did not and were not expected to act exactly like “seductress-spies,” but there were some similarities. Civilian women were expected to utilise perceptions that women were ignorant and apolitical to their advantage. They were also expected to capitalise on their femininity to appear innocent and approach enemy men in order to ferret out intelligence and to get these men to do things they otherwise would not have done. Moreover, in the 1930s and early 1940s some officials found that civilian women who had been deemed promiscuous locally or were prostitutes made good recruits because they thought that having already rejected Confucian values they would be relatively tolerant of the risks and more willing to be seen in public. Ultimately, this thesis argues that while CCP Woman-Work efforts in the first half of the 20th century sought, on paper at least, to reject and eradicate what they saw as detrimental stereotypes about women, in practice civilian women were sometimes mobilised to engage in clandestine activities during wartime based on aspects of these stereotypes and perceptions. As such, this thesis contributes to the study of female espionage in China by examining those who were attached to the peripheries of CCP intelligence operations. It also contributes to the study of how some of the traditional values and gender norms regarding Chinese women continued to exist in the 20th century despite the CCP’s official pledge to change them.